COVID-19 and Emotional Variables in a Sample of Chileans - González-Tovar, Mariela; Hernández-Rodríguez, Sergio (Frontiers in Psychology, 2021)
Introduction. During the Coronavirus (COVID-19) pandemic, a set of daily stressors are being experienced, all this affects people's mental health, leading them to have a set of emotional disturbances. Little is known about how people's age can influence their emotional well-being in the face of prolonged stress generate by the pandemic. Objective. To clarify the presence of emotional aspects such as emotional expressiveness and the frequency of positive and negative affections in people with different age in times of crisis. Method. The final sample included 297 Chileans between 22 and 68 years old (M= 38.51, SD = 13.85), recruited through an online survey with the appropriate written informed consent. The study was carried out when the pandemic was spreading in Chile. Results. The findings revealed age differences in emotional expressivity and the type of affections experienced. The expression of emotions was more affected by negative affections, the age and the gender of the people. While the avoidance of this emotional expression, by age and affections both positive and negative. Age was a significant predictor of emotional expressiveness. Discussion. Findings suggests that the associations between both variables, varied according to the age group of the people. Furthermore, this finding proposes that although older people are facing the persistent and serious threat of COVID-19, they show better emotional functioning. Which would help to better understand the interaction of both positive and negative life experiences in times of crisis.